The Moderating Effect of Within‐Group Similarity on Change in a Strengths‐Based Programme for Incarcerated Young Men. (22nd May 2014) - Viola, Wendy Elaine; Mankowski, Eric S.; Gray, Mary Elisabeth
Abstract: Many youth who are incarcerated within juvenile correctional facilities experience mental health disorders, histories of victimization and suicide ideation. Strengths‐based intervention programmes are intended to enhance participants' resilience against such challenges. However, little is known about how the composition of intervention groups contributes to programmes' efficacy. This study addresses the impact of within‐group similarity on the success of a strengths‐based intervention for incarcerated young men ( n = 141). Similarity was assessed in terms of self‐reported demographics and behaviours and belief systems. Youths' masculine ideology, caring and cooperative behaviours, ethnic pride and respect for differences, self‐efficacy regarding education and non‐violence, and attitudes about criminal behaviour were measured before and after intervention. Results indicate that participants' caring and cooperative behaviour increased during the intervention. However, their education‐related self‐efficacy was reduced, and the perceived benefits of criminal activity increased. These changes were moderated by group composition: less similarity between participants and their group members was associated with less negative change. In the context of juvenile corrections facilities, where staying the same may be a relatively positive outcome, perhaps the more relevant question is not which processes and characteristics of others better enable youth to change but which experiences help them retain positive aspects of themselves. Copyright © 2014 John Wiley & Sons, Ltd.